Genotypic Antimicrobial Resistance Profiles of Diarrheagenic Escherichia coli and Nontyphoidal Salmonella Strains Isolated from Children with Diarrhea and Their Exposure Environments in Ethiopia - Belina D; Gobena T; Kebede A; Chimdessa M; Hald T (Infection and Drug Resistance)
Dinaol Belina,1,2 Tesfaye Gobena,3 Ameha Kebede,2 Meseret Chimdessa,2 Tine Hald4 1College of Veterinary Medicine, Haramaya University, Dire Dawa, Ethiopia; 2School of Biological Sciences and Biotechnology, Haramaya University, Dire Dawa, Ethiopia; 3College of Health and Medical Sciences, Haramaya University, Harar, Ethiopia; 4National Food Institute, Technical University of Denmark, Lyngby, DenmarkCorrespondence: Dinaol Belina, Email belina.dinaol@gmail.comBackground: Antimicrobial resistance (AMR) poses a significant global threat, particularly in low- and middle-income countries, such as Ethiopia, where surveillance is limited. This study aimed to predict and characterize the AMR profiles of diarrheagenic Escherichia coli (DEC) and nontyphoidal Salmonella (NTS) strains isolated from human, animal, food, and environmental samples using whole genome sequencing.Methods: A total of 57 NTS and 50 DEC isolates were sequenced on an Illumina NextSeq 550. The ResFinder and PointFinder tools were employed to identify antimicrobial resistance genes (ARGs) and point mutations. Salmonella serotypes were determined using SeqSero.Results: The analysis identified at least one ARG in every NTS sample and 78% of the DEC isolates, with 22 distinct ARGs in the NTS samples and 40 in the DEC samples. The most prevalent ARGs were aac(6′)-Iaa and aph(3′)-Ib, which predict aminoglycoside resistance in 100% of NTS and 54% of DEC isolates, respectively. Other commonly identified ARGs include sul 2, aph(6)-Id, blaTEM-1B, and tet(A), which confer resistance to folate inhibitors, aminoglycosides, β-lactams, and tetracycline. Some ARGs predicted phenotypic multidrug resistance in both DEC and NTS isolates. All identified β-lactam ARGs, except for blaTEM− 1D, conferred resistance to more than three antibiotics. Interestingly, blaCTX-M-15 was found to confer resistance to nine antibiotics, including third-generation cephalosporins, in 18% of DEC and 3.5% of NTS isolates. DEC isolates from children exhibited the highest ARG diversity. Notably, genes such as aph(3″)-Ib, aph(6)-Id, sul 2, and tet(A) were detected across all sample types, including water sources, although some ARGs were exclusive to specific sample types. Point mutations mediating AMR were detected in several genes, with mutations associated with nucleotide substitution being the most frequent.Conclusion: This genotypic AMR profiling revealed the presence of widespread drug-resistant NTS and DEC strains in Ethiopia. Robust and sustained AMR surveillance is essential for monitoring the emergence and spread of these resistant pathogens.Keywords: antimicrobial resistance, Ethiopia, foodborne pathogens, whole genome sequence